STUDI LITERATUR : EFEKTIVITAS VIDEO TUTORIAL BERBASIS ART-BASED LEARNING DALAM PEMBELAJARAN SENI TARI - Khosy Berlian Putry; Suci Fajrina; Rosta Minawati; Iswandi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the effectiveness of using Art-Based Learning (ABL)-based video tutorials in dance learning through a literature review approach. Limited practice time and students’ difficulties in understanding and memorizing dance movement sequences pose challenges in the process of dance education in schools. Video tutorials are considered a learning medium that can provide flexible, engaging, and contextual learning experiences, while the ABL approach emphasizes artistic experiences that encourage reflection, imagination, and creativity among students. The research method employed is a literature review, involving the examination of various scientific articles, books, and relevant research reports. The review procedure includes topic selection, literature search, analysis and synthesis of previous research findings, and systematic presentation of results. The findings indicate that ABL-based video tutorials are effective in improving movement technique skills, understanding aesthetic values, and enhancing appreciation of dance culture. Furthermore, the application of ABL through digital media provides opportunities for students to learn independently, create, and internalize artistic values through personal experiences. Therefore, ABL-based video tutorials represent a potential learning medium to strengthen dance education in the digital era